A Rare Adult Case of Sacroiliitis Due to Poststreptococcal Reactive Arthritis - Emre ADIGÜZEL,; Ümmügülsüm DOĞAN DURAN,; Yasin DEMİR,; Sebahattin SARI,; İsmail SAFAZ, (Archives of Rheumatology, 2015)
Poststreptococcal reactive arthritis is a type of sterile arthritis which occurs after a betahemolytic streptococcal throat or skin infection. It was defined as scarlatinal arthritis in 1959. Poststreptococcal reactive arthritis is a kind of non-migratory arthritis that usually affects the knee and ankle joints. Although rare, small joints and the axial skeleton may also be involved. In this report, we present a patient with unilateral sacroiliac joint inflammation and adductor enthesopathy following an upper respiratory tract infection who was eventually diagnosed with poststreptococcal reactive arthritis.